Indirect electrochemical reduction of nitrate in water using zero-valent titanium anode: Factors, kinetics, and mechanism. (15th June 2019) - Yao, Fubing; Yang, Qi; Zhong, Yu; Shu, Xiaoyu; Chen, Fei; Sun, Jian; Ma, Yinghao; Fu, Zhiyan; Wang, Dongbo; Li, Xiaoming
Abstract: In this study, indirect electrochemical reduction with zero-valent titanium (ZVT) as anode successfully achieved the selective nitrate removal from simulated groundwater. The maximum nitrate removal efficiency and N2 selectivity reached to 83.4% and 78.5% after 12 h, respectively. Experimental results demonstrated that the gaseous by-products (NO and N2 O) were negligible and the nitrate reduction process could be well depicted by pseudo-first-order kinetic model. Decreasing the pH value of electrolyte was favorable to electrical energy utilization efficiency and nitrate removal. The chloride ultimately showed inhibitory effects on electrochemical reduction of nitrate. During the electrochemical reaction, the ZVT lost electrons to generate the reducing agents (Ti 3+ and Ti 2+ ), which could afford electrons for nitrate reduction and form the solid by-products TiO2.4 Cl0.2 N0.1 . A 2-stage strategy, indirect electrochemical reduction + hypochlorite treatment (pre-reduction + post-oxidation), was developed to completely remove nitrate and the long-term performance of nitrate reduction was comprehensively evaluated. The effluent nitrate steadily kept at 8.8 mg N/L during 120 h continuous operation when the influent nitrate concentration was 25.9 mg N/L. Simultaneously, nitrite concentration was lower than 0.01 mg N/L, and ammonium and Ti ions were not detected in the effluent. Graphical abstract: Image 1 Highlights: The current density and pH greatly influenced on electro-reduction of nitrate. The chloride ultimately showed inhibitory effects on electro-reduction of nitrate. The reaction process could be well depicted by pseudo-first-order kinetic model. Ti 3+ and Ti 2+ afforded electrons for nitrate reduction and formed TiO2.4 Cl0.2 N0.1 . Nitrate could be completely converted into N2 by pre-reduction + post-oxidation.